SURGICAL METHOD FOR UNCOVERING OF THE IMPLANT AT TWO-STAGE IMPLANTATION PROCEDURES - O.V. Dobrovolska; A.V. Dobrovolskyi; I.V. Pavlish; L.A. Lugovaya (Ukrainian Medical Stomatological Academy, 2016)
Dental implantation today has filled its respective niche in patient rehabilitation, having become part of everyday dental routine. There exists a rather wide range of various dental implantation techniques which can be divided into the following groups: those requiring elevation of flap and the ones which do not need any soft-tissue manipulation; dental implantation performed in combination with bone or soft-tissue augmentation or without it (in stages); single stage and two-stage implantation procedures; implantation with immediate and delayed loading act. All these techniques seek to correct edentulous defects and restore natural functions, as well as ensure esthetics. Today an implant supported orthopedic construction is expected to both mimic the color, texture and shape of a natural tooth, and ensure adequate soft-tissue contour and pink aesthetics around the crown. Rendering correct gingival aesthetics is quite a complicated mission for a dentist to perform. There are various methods used for uncovering of the implant, including the following. The soft tissues over the cover screw may be removed with a tissue punch. This is easiest when the implant itself may be palpated, or if there is sufficient keratinized tissue. Its advantages include minimal trauma and very little discomfort for the patient. Other methods that may be employed are the full-thickness flap technique and the crestal incision. These methods also require sufficient attached tissue. They have the advantage of direct visualization of the bone area and not having to rely on tactile sense alone. If there is insufficient keratinized tissue, then the partial-thickness flap gingivectomy technique is used. This method is more painful and requires longer healing time. Supraperiosteal flaps to gain fixed gingiva around the implant are thought to be advantageous. Soft tissue factors, epithelial and fibrous, are important in long-term retention of osseointegrated implants. Meticulous surgery and care with surgical soft tissue flap design and apposition on completion of operative procedures is essential. A true gingival crevice cannot in reality be formed but a sound, infection-free peri-implant epithelial cuff can be. Whether combined use of guided tissue regeneration techniques may aid this aspect of the technique remains under investigation. The local flora is altered due to the non-physiological anatomy.